ANALISIS POTENSI PANTAI PERERENAN SEBAGAI DAYA TARIK WISATA DI DESA PERERENAN BADUNG BALI - Gusti Ayu Mira Santika Dewi; Retno Juwita Sari; Ni Luh Gde Sari Dewi Astuti (MSJ : Majority Science Journal, 2023)
Analysis of the potential of Pererenan Beach to become a tourist attraction in Pererenan Village is the subject of discussion in this study. The purpose of this study (1) to find out the tourism potential of Pererenan Beach so that it can be developed as a tourist attraction. (2) to find out the opportunities and challenges faced by the management regarding the potential development of Pererenan beach as a tourist attraction. This study uses a descriptive qualitative approach. Data was collected through observation techniques, interviews, literature and documentation. This study uses concepts based on 5A, namely attractions, accessibility, amenities, activities, and comfort. On the opportunities and challenges faced by the management of Pererenan Beach it was found that the management parties were the Village Government, Village Communities and Traders. The results of this study found that apart from having beautiful natural potential and being used as a place to see the sunset, Pererenan Beach has cultural potential in the form of traditional kite competitions which are held every year as well as the potential to develop surfing sports. There are several things in the management of the Pererenan Beach tourist destination that need to be optimized, namely the lack of management of tourist attractions, especially shelter facilities, parking lots, public toilets and waste management, lack of tourist facilities and infrastructure, incompetent human resources, and undeveloped products. maximum for tourists. The results of this study can be used as a reference for improving the development of Pererenan Beach Tourism Attraction in the future.